Pendampingan Guru MTs Dan MA Dalam Menyiapkan Pembelajaran Pada Kurikulum Merdeka - Isna Rezkia Lukman; Widya; Ucia Mahya Dewi (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The mentoring of teachers in the implementation of the Merdeka Curriculum is a strategic step to ensure the success of educational reform in Indonesia. At MTs and MA Darul Falah, this mentoring includes planning, execution, and evaluation, focusing on enhancing teachers' competencies as well as applying innovative teaching strategies and methods. The main objective of this mentoring is to improve the understanding of teachers at MTs and MA Darul Falah regarding the principles and practices of the Merdeka Curriculum. This approach uses a qualitative method with observation and documentation study. Observations were conducted during face-to-face Forum Group Discussions (FGD) and during mentoring sessions at MTs and MA Darul Falah. The results of the mentoring show that teachers experienced an increase in their understanding and skills related to the Merdeka Curriculum. The service activities resulted in an average posttest score of 8.8, with an n-gain increase reaching 0.81, categorized as very good. Additionally, the mentoring was effective in creating Merdeka Curriculum administrative instruments, achieving a suitability rate of 87.5%. The high posttest scores indicate successful knowledge transfer, while the high satisfaction level of participants reflects strong approval of the training and mentoring provided. Active discussions and experience sharing during the activities allowed teachers to find joint solutions to learning challenges. It is hoped that this mentoring will prepare teachers at MTs and MA Darul Falah to prepare curriculum changes, enhance their motivation and confidence in teaching according to the Merdeka Curriculum, and foster collaboration and innovation in teaching practices.